| library /*isNonNullableByDefault*/; |
| // |
| // Problems in library: |
| // |
| // pkg/front_end/testcases/instantiate_to_bound/multiple_strongly_connected.dart:41:9: Error: Type 'T' is a bound of itself via 'U', 'Y', 'Z'. |
| // Try breaking the cycle by removing at least on of the 'extends' clauses in the cycle. |
| // class I<T extends U, U extends Y, V extends Function(W), W extends Function(X), |
| // ^ |
| // |
| import self as self; |
| import "dart:core" as core; |
| |
| class A<X extends core::Object? = dynamic> extends core::Object { |
| synthetic constructor •() → self::A<self::A::X%> |
| : super core::Object::•() |
| ; |
| } |
| class B<X extends core::Object? = dynamic, Y extends core::Object? = dynamic> extends core::Object { |
| synthetic constructor •() → self::B<self::B::X%, self::B::Y%> |
| : super core::Object::•() |
| ; |
| } |
| class C<X extends core::Object? = dynamic, Y extends core::Object? = dynamic> extends core::Object { |
| synthetic constructor •() → self::C<self::C::X%, self::C::Y%> |
| : super core::Object::•() |
| ; |
| } |
| class D<X extends self::A<self::D::X> = self::A<dynamic>, Y extends self::A<self::D::Y> = self::A<dynamic>> extends core::Object { |
| synthetic constructor •() → self::D<self::D::X, self::D::Y> |
| : super core::Object::•() |
| ; |
| } |
| class E<W extends self::B<self::E::W, self::E::X> = self::B<dynamic, dynamic>, X extends self::C<self::E::W, self::E::X> = self::C<dynamic, dynamic>, Y extends self::B<self::E::Y, self::E::Z> = self::B<dynamic, dynamic>, Z extends self::C<self::E::Y, self::E::Z> = self::C<dynamic, dynamic>> extends core::Object { |
| synthetic constructor •() → self::E<self::E::W, self::E::X, self::E::Y, self::E::Z> |
| : super core::Object::•() |
| ; |
| } |
| class F<V extends core::num, W extends self::B<self::F::W, self::F::X> = self::B<dynamic, dynamic>, X extends self::C<self::F::W, self::F::X> = self::C<dynamic, dynamic>, Y extends self::B<self::F::W, self::F::X> = self::B<self::B<dynamic, dynamic>, self::C<dynamic, dynamic>>, Z extends self::C<self::F::Y, self::F::Z> = self::C<self::B<self::B<dynamic, dynamic>, self::C<dynamic, dynamic>>, dynamic>> extends core::Object { |
| synthetic constructor •() → self::F<self::F::V, self::F::W, self::F::X, self::F::Y, self::F::Z> |
| : super core::Object::•() |
| ; |
| } |
| class G<V extends core::num, W extends self::B<self::G::V, self::G::X> = self::B<core::num, dynamic>, X extends self::C<self::G::W, self::G::V> = self::C<dynamic, core::num>, Y extends self::B<self::G::W, self::G::X> = self::B<self::B<core::num, dynamic>, self::C<dynamic, core::num>>, Z extends self::C<self::G::Y, self::G::Z> = self::C<self::B<self::B<core::num, dynamic>, self::C<dynamic, core::num>>, dynamic>> extends core::Object { |
| synthetic constructor •() → self::G<self::G::V, self::G::W, self::G::X, self::G::Y, self::G::Z> |
| : super core::Object::•() |
| ; |
| } |
| class H<S extends self::A<self::H::S> = self::A<dynamic>, T extends self::B<self::H::T, self::H::U> = self::B<dynamic, dynamic>, U extends self::C<self::H::T, self::H::U> = self::C<dynamic, dynamic>, V extends self::A<self::H::V> = self::A<dynamic>, W extends self::H::S = self::A<dynamic>, X extends self::H::T = self::B<dynamic, dynamic>, Y extends self::H::U = self::C<dynamic, dynamic>, Z extends self::H::V = self::A<dynamic>> extends core::Object { |
| synthetic constructor •() → self::H<self::H::S, self::H::T, self::H::U, self::H::V, self::H::W, self::H::X, self::H::Y, self::H::Z> |
| : super core::Object::•() |
| ; |
| } |
| class I<T extends invalid-type, U extends self::I::Y% = invalid-type, V extends (self::I::W) → dynamic = (Never) → dynamic, W extends (self::I::X) → dynamic = (Never) → dynamic, X extends (self::I::V) → dynamic = (Never) → dynamic, Y extends self::I::Z% = invalid-type, Z extends self::I::T% = invalid-type> extends core::Object { |
| synthetic constructor •() → self::I<self::I::T%, self::I::U%, self::I::V, self::I::W, self::I::X, self::I::Y%, self::I::Z%> |
| : super core::Object::•() |
| ; |
| } |
| class J<S extends (self::J::U) → self::J::T = (Never) → dynamic, T extends (self::J::S) → self::J::U = (Never) → dynamic, U extends (self::J::T) → self::J::S = (Never) → dynamic, V extends self::J::W = dynamic, W extends self::J::X = dynamic, X extends (self::J::V) → self::J::Y = (Never) → dynamic, Y extends self::J::Z = dynamic, Z extends self::J::X = dynamic> extends core::Object { |
| synthetic constructor •() → self::J<self::J::S, self::J::T, self::J::U, self::J::V, self::J::W, self::J::X, self::J::Y, self::J::Z> |
| : super core::Object::•() |
| ; |
| } |
| static field self::D<self::A<dynamic>, self::A<dynamic>> d = throw ""; |
| static field self::E<self::B<dynamic, dynamic>, self::C<dynamic, dynamic>, self::B<dynamic, dynamic>, self::C<dynamic, dynamic>> e = throw ""; |
| static field self::F<core::num, self::B<dynamic, dynamic>, self::C<dynamic, dynamic>, self::B<self::B<dynamic, dynamic>, self::C<dynamic, dynamic>>, self::C<self::B<self::B<dynamic, dynamic>, self::C<dynamic, dynamic>>, dynamic>> f = throw ""; |
| static field self::G<core::num, self::B<core::num, dynamic>, self::C<dynamic, core::num>, self::B<self::B<core::num, dynamic>, self::C<dynamic, core::num>>, self::C<self::B<self::B<core::num, dynamic>, self::C<dynamic, core::num>>, dynamic>> g = throw ""; |
| static field self::H<self::A<dynamic>, self::B<dynamic, dynamic>, self::C<dynamic, dynamic>, self::A<dynamic>, self::A<dynamic>, self::B<dynamic, dynamic>, self::C<dynamic, dynamic>, self::A<dynamic>> h = throw ""; |
| static field self::I<invalid-type, invalid-type, (Never) → dynamic, (Never) → dynamic, (Never) → dynamic, invalid-type, invalid-type> i = throw ""; |
| static field self::J<(Never) → dynamic, (Never) → dynamic, (Never) → dynamic, dynamic, dynamic, (Never) → dynamic, dynamic, dynamic> j = throw ""; |
| static method main() → dynamic {} |